2007
DOI: 10.1007/bf03178409
|View full text |Cite
|
Sign up to set email alerts
|

Extrapolated surface dose measurements using a NdFeB magnetic deflector for 6 MV x-ray beams

Abstract: Extrapolated surface dose measurements have been performed using radiographic film to measure 2-Dimensional maps of skin and surface dose with and without a magnetic deflector device aimed at reducing surface dose. Experiments are also performed using an Attix parallel plate ionisation chamber for comparison to radiographic film extrapolation surface dose analysis. Extrapolated percentage surface dose assessments from radiographic film at the central axis of a 6 MV x-ray beam with magnetic deflector for field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Film dosimeters offer permanent records of the ionizing dose distribution measured at high resolutions with the evident advantages of being 2D detectors. Due to the high-atomic-number material constituents, silver halide films are traditionally used; however, these films have the disadvantage of pronounced energy dependence (Damrongkijudom et al, 2007;Palm et al, 2004). This could introduce systematic errors for most usual treatment plans (Arjomandy et al, 2010;Rath et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Film dosimeters offer permanent records of the ionizing dose distribution measured at high resolutions with the evident advantages of being 2D detectors. Due to the high-atomic-number material constituents, silver halide films are traditionally used; however, these films have the disadvantage of pronounced energy dependence (Damrongkijudom et al, 2007;Palm et al, 2004). This could introduce systematic errors for most usual treatment plans (Arjomandy et al, 2010;Rath et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these changes can be attributed to variations in electron contamination and phantom scatter. Large variations are observed for changes in beam parameters such as field size, the use of beam modifying devices and the beam angle of incidence (Butson et al 1996, Zhu and Palta 1998, Hounsell and Wilkinson 1999, Damrongkijudom et al 2007 or for changes in the material which may be in a direct or indirect path of the radiation beam in question. It has been shown that the skin dose can be adequately measured with the EBT Gafchromic, radiochromic film (Devic et al 2006).…”
Section: Introductionmentioning
confidence: 99%